Gefitinib in Non Small Cell Lung Cancer. (23rd May 2011) - Costanzo, Raffaele; Piccirillo, Maria Carmela; Sandomenico, Claudia; Carillio, Guido; Montanino, Agnese; Daniele, Gennaro; Giordano, Pasqualina; Bryce, Jane; De Feo, Gianfranco; Di Maio, Massimo; Rocco, Gaetano; Normanno, Nicola; et al.
Abstract : Gefitinib is an oral, reversible, tyrosine kinase inhibitor of epidermal growth factor receptor (EGFR) that plays a key role in the biology of non small cell lung cancer (NSCLC). Phase I studies indicated that the recommended dose of gefitinib was 250 mg/day. Rash, diarrhea, and nausea were the most common adverse events. The positive results obtained in early phase 2 clinical trials with gefitinib were not confirmed in large phase 3 trials in unselected patients with advanced NSCLC. The subsequent discovery that the presence of somatic mutations in the kinase domain of EGFR strongly correlates with increased responsiveness to EGFR tyrosine kinase inhibitors prompted phase 2 and 3 trials with gefitinib in the first line-treatment of EGFR-mutated NSCLC. The results of these trials have demonstrated the efficacy of gefitinib that can be now considered as the standard first-line treatment of patients with advanced NSCLC harbouring activating EGFR mutations.